TAILORING EXTENSIVE READING PROGRAMS FOR EAP STUDENTS IN ISLAMIC HIGHER EDUCATION: PEDAGOGICAL INSIGHTS AND OUTCOMES - Indrawati, Johara; Asmira, Mita (Universitas Tanjungpura, 2025)
This research addresses the gap in the literature regarding tailored Extensive Reading Program (ERP) in English for Academic Purposes (EAP) within Islamic higher education. Recognizing the need for context-specific language interventions, the study aimed to investigate the pedagogical insights and outcomes of implementing a Tailored ERP at Universitas Islam Internasional Darullughah Wadda